Driving Sustainable Loyalty: Does Green Quality Mediate the Impact of Green Banking in Sharia Banks? - Anisa Rahmawati; Hilmy Baroroh (Faculty Of Islamic Economics and Business, 2026)
Research Purpose: This study aims to analyze the influence of green banking practices, namely digital banking, green financing, green infrastructure, and green services, on customer loyalty at Bank Syariah Indonesia, with green service quality as a mediating variable. Method: The research method uses a quantitative approach with a purposive sampling technique involving 160 BSI customers in Yogyakarta City. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the help of WarpPLS 8.0 software.Research Findings: The results show that all dimensions of green banking have a positive and significant effect on customer loyalty, with digital banking having the most dominant influence (β = 0.390, p < 0.001). Furthermore, green service quality is proven to mediate the relationship between green infrastructure and green services on customer loyalty, but it does not mediate the relationship between digital banking and green financing.Recommendations and Novelty: These findings emphasize the importance of optimal implementation of green banking in enhancing customer loyalty in Islamic banking in a sustainable and competitive manner. This study takes a relevant approach and strengthens it by introducing a mediating variable, namely green service. Tujuan penelitian: Penelitian ini bertujuan untuk menganalisis pengaruh praktik perbankan hijau, yaitu perbankan digital, pembiayaan hijau, infrastruktur hijau, dan layanan hijau, terhadap loyalitas nasabah di Bank Syariah Indonesia, dengan kualitas layanan hijau sebagai variabel mediasi.Metode: Metode penelitian menggunakan pendekatan kuantitatif dengan teknik purposive sampling yang melibatkan 160 nasabah BSI di Kota Yogyakarta. Data dianalisis menggunakan Structural Equation Modeling-Partial Least Squares (SEM-PLS) dengan bantuan software WarpPLS 8.0.Temuan penelitian: Hasil penelitian menunjukkan bahwa semua dimensi perbankan hijau memiliki pengaruh positif dan signifikan terhadap loyalitas nasabah, dengan perbankan digital memiliki pengaruh paling dominan (β = 0,390, p < 0,001). Selain itu, kualitas layanan hijau terbukti memediasi hubungan antara infrastruktur hijau dan layanan hijau terhadap loyalitas nasabah, tetapi tidak memediasi hubungan antara perbankan digital dan pembiayaan hijauKontribusi dan Kebaruan: Temuan ini menekankan pentingnya penerapan perbankan hijau secara optimal dalam meningkatkan loyalitas pelanggan di perbankan Islam secara berkelanjutan dan kompetitif. Studi ini menggunakan pendekatan yang relevan dan memperkuatnya dengan memperkenalkan variabel mediasi, yaitu layanan hijau.